Intelligent control strategies for grid-connected photovoltaic wind hybrid energy systems using ANFIS - Thiruveedula Madhu Babu; Kalagotla Chenchireddy; Kotha Kalyan Kumar; Vasukul Nehal; Sappidi Srihitha; Marikal Ram Vikas (Institute of Advanced Engineering and Science, 2024)
This study proposes intelligent control strategies for optimizing the grid integration of photovoltaic (PV) and wind energy in hybrid systems using an adaptive neuro-fuzzy inference system (ANFIS). The ANFIS control aims to enhance grid stability, improve power management, and maximize renewable energy (RE) utilization. The hybrid system's performance is evaluated through simulations, considering various environmental conditions and load demands. Results demonstrate the effectiveness of the proposed ANFIS-based control in dynamically adjusting the power output from PV and wind sources, ensuring efficient grid-connected operation. The findings underscore the potential of intelligent control strategies to contribute to the reliable and sustainable integration of RE into the grid.